Business Impact Analysis Terkait Penanganan dan Pemulihan Terhadap Bencana di PT Bank XYZ - Rubil, Rubil (ComTech: Computer, Mathematics and Engineering Applications, 2012)
For each company, disasters may have diverse impacts either financially or non-financially. Therefore, a company requires a business continuity plan. One important factor in developing such plan is Business Impact Analysis (BIA). With BIA, a company can identify and analyze Critical Business Functions (CBFs) and potential impacts on the business whether operationally or financially, and further, business recovery priority, strategy and solution can be determined following a disaster.Methodologies used in developing this BIA are quantitativeand qualitative where for aspects related to financials, quantitive method is used. Meanwhile, for those aspects\ related to non-financial areas, qualitative method is used. The development of this BIA was done through the dissemination of questionnaires to 62 business units in PT Bank XYZ. To draw the BIA, eight parameters were used, where as for the final result, there were three criticality levels found in the business units of PT Bank XYZ, i.e. very critical level - 18 business units (29%), critical level - 23 business units (37%) and less critical level – 21 business units (34%). In addition, there were 71 applications used by CBFs. Based on the results of this study, PT Bank XYZ can determine the priority and key strategies for business units that require handling and recovery when a disaster occurs to maintain the bank's business operation's continuity and sustainability.Withthat, the company can minimize the potential loss resulted from a disaster.